What is the Helicobacter pylori Global Reinfection Rate? - Julie Parsonnet (Canadian Journal of Gastroenterology)
Reinfection with any organism is related to the force of infection in the population and on both innate and acquired immunity to infection. Little is yet known about primary immune protection against Helicobacter pylori. Some data suggest that children can be recurrently infected, spontaneously eliminating the organism only to be infected again and again until the organism takes hold. This pattern of recurrent infection is not observed in patients who receive eradication therapy for chronic infection. After eradication of infection, the rate of reinfection is probably slightly lower than the primary infection rate in that age group, suggesting some level of acquired immunity. In developed countries, reinfection of adults in unusual, and recurrence usually repesents failure of primary eradicaton rather than new infection. Some cases of reinfection do occur, however. Given that acquired immunity probably varies little from population to population, reinfections will most likely occur in areas where the force of infecton is high, ie, where both the prevalence of infection and the opportunities for transmission are high.